ANALISIS KELENGAKAPAN PENDOKUMENTASIAN PELAYANAN KEBIDANAN DI WILAYAH KERJA PUSKESMAS LUBUKBUAYA KOTA PADANG - Zulfita Zulfita; Eka Putri Primasari; Putri Nelly Syofiah (Universitas Fort De Kock, 2020)
Midwifery documentation has a large portion in the patient's clinical record that informs certain factors or situations during the midwifery care provided. In Puskesmas Lubuk Buaya, there are 94.12% of midwives who dont report the documentation of midwifery perfectly in according to requirements that must be reported. The research aims to analyze problems related to the completeness of midwife documentation of midwifery services in the work area of Puskesmas Lubuk Buaya. The method of this study is qualitative. This research was conducted in August - October 2019. The results of research was founded, Puskesmas Lubuk Buaya had followed according to government policy. Funding, human resources and infrastructure are quite adequate, just how to use and optimize it and how disciplined the officers are in using it. The planning of the Puskesmas Lubuk Buaya has been going well. However, for the completeness of documentation of midwives in providing midwifery services, SOAP documentation has not been applied to each patient. Midwives tend not to make SOAP because SOAP is not a mandatory report that must be reported every month to the Puskesmas. Evaluations are reviewed when submitting monthly report collections which are then recapitulated by the Puskesmas in the Puskesmas monthly report.